Heat transfer and entropy analysis of three different types of heat exchangers operated with nanofluids - Leong, K.Y.; Saidur, Rahman; Khairulmaini, M.; Michael, Z.; Kamyar, A. (International Communications in Heat and Mass Transfer, 2012)
The development of nanotechnology has witnessed an emergence of new generation of heat transfer fluids known as nanofluids. Nanofluids are used as coolants which provide excellent thermal performance in shell and tube heat exchangers. However, the viscosity of these fluids increases with the addition of nanoparticles. Furthermore, the performance of these heat exchangers is influenced by the arrangement of baffles. Thus, in this paper, the study focuses on the heat transfer and entropy analysis of segmental, 25Â° and 50 helical baffles shell and tube heat exchangers. Heat transfer rate of the 25 helical baffles heat exchanger found to be the highest among the three heat exchangers studied in this research. Study indicates that shell and tube heat exchanger with 50Â° helical baffles exhibits lowest entropy generation among three different heat exchangers.